Organizational Culture As A Moderation Of Influence Of Professional Commitment And Moral Reasoning On Independent Auditors' Ethical Decisions - Tama, Gede Mandirta; Yasa, Gerianta Wirawan; Ramantha, I Wayan; Rasmini, Ni Ketut (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study aims to provide empirical evidence regarding the effect of professional commitment and moral reasoning on ethical decisions and the ability of organizational culture to moderate the effect of professional attention and moral reasoning on ethical decisions. The population of this study was independent auditors of the capital market at KAPs in the East Java and West Java Regions who were actively registered with the OJK. The sampling method used the total sampling technique and obtained a sample of 59 people. The data analysis technique used is the PLS model. The results showed that professional attention has a positive effect on ethical decisions, moral reasoning has a positive effect on ethical decisions, organizational culture strengthens the effect of positive professional attention on ethical decisions, and organizational culture strengthens the effect of positive moral reasoning on ethical decisions.